Frequency of nurse-provided spiritual care: An international comparison - Taylor, Elizabeth Johnston (2022)
Aims and objectives: To compare the frequency of nurse-provided spiritual care across diverse cultures. Background: Given an ethical imperative to respect patient spirituality and religiosity, nurses are increasingly taught and expected to provide spiritual care. Although nurses report positive attitudes toward spiritual care, they typically self-report providing it infrequently. Evidence about the reported frequency of spiritual care is constrained by substantial variation in its measurement. Design: This cross-sectional, descriptive study involved secondary analysis of data collected in multiple sites globally using one quantitative instrument. Methods: Data were collected from practicing nurses using the Nurse Spiritual Care Therapeutics Scale and analysed using descriptive statistics and a meta-analysis procedure with random-effect modelling. Datasets from 16 studies completed in Indonesia, Iran, Malaysia, Philippines, Portugal, Taiwan, Turkey and the United States contributed to a pooled sample (n = 4062). STROBE guidelines for cross-sectional observational studies were observed. Results: Spiritual care varied between countries and within countries. It was slightly more frequent within Islamic cultures compared with predominantly Christian cultures. Likewise, frequency of spiritual care differed between nurses in palliative care, predominantly hospital/inpatient settings, and skilled nursing homes. Overall, “Remaining present…” was the most frequent therapeutic, whereas documenting spiritual care and making arrangements for the patient's clergy or a chaplain to visit were among the most infrequent therapeutics. Conclusions: In widely varying degrees of frequency, nurses around the world provide care that is cognisant of the spiritual and religious responses to living with health challenges. Future research should be designed to adjust for the multiple factors that may contribute to nurses providing spiritual care. Relevance to clinical practice: Findings offer a benchmark and begin to inform nurse leaders about what may be normative in practice. They also encourage nurses providing direct patient care that they are not alone and inform educators about what instruction future nurses require.